Potted plants keep indoors healthy - Janakiram, T.; Jain, Ritu; Kumar, P. Pavan (Indian Horticulture, 2019)
Introduction: In India, urban population is increasing rapidly and by 2050 more than 60% population will reside in urban and peri-urban areas. Since, city dwellers spend 90% of their time indoors and indoor air quality is a major health issue. Components of furniture, fabrics, fittings, paints, glues, varnishes, computers, printers, solvents, detergents, shampoos, cosmetics, etc. emit volatile compounds causing many diseases like asthma, strokes, heart attacks, sudden infant death syndrome, low birth weights, cancers, cardiovascular problems, schizophrenia and other mental illnesses, sick building syndrome etc. Indoor potted plants are the best solution to address these issues as indoor plants enhance indoor environment quality, improves efficiency, reduce noise and dust levels etc. About two plants per 100 square feet or two plants in a small office keep the air pure and healthy. These can be used in balcony, windows, corridors, varandah, patio, kitchen etc.